Object-In-Fluid Framework in Modeling of Blood Flow in Microfluidic Channels - Cimrak, Ivan; Bachrata, Katarina; Bachraty, Hynek; Jancigova, Iveta; Tothova, Renata; Busik, Martin; Slavik, Martin; Gusenbauer, Markus (Communications - Scientific letters of the University of Zilina, 2016)
We present a fully three-dimensional computational model of red blood cells and their flow in a fluid. This model includes all components necessary to capture important physical and biological aspects of the cell flow. It comprises descriptions of elasticity of the cell membrane, cell-cell interactions, two-way cell-fluid interaction, and adhesion of cell to surfaces. Using this model, we analyze different processes involving flow of cells. We present the results of ongoing research concerning the development of model for cell adhesion, the analysis of microfluidic devices with periodic obstacle arrays, the optimization of microfluidic connectors and biological process of red blood cells formation from reticulocytes.